The Belarusian Shtetl History and Memory - Kopčenova, Irina Vladimirovna (Jews in Eastern Europe Series, 2023)
"For centuries Jewish shtetls were an active part of Belarusian life; today, they are gone. The Belarusian Shtetl is a landmark volume which offers, for the first time in English, an illuminating look at the shtetls' histories, the lives lived and lost in them, and the memories, records, and physical traces of these communities that remain today. Since 2012, under the auspices of the Sefer Center for University Teaching of Jewish Civilization, teams of scholars and students from many different disciplines have returned to the sites of former Jewish shtetls in Belarus to reconstruct their past. These researchers have interviewed a wide range of both Jews and non-Jews to find and document traces of Shtetl history, to gain insights into community memories, and to discover surviving markers of identity and ethnic affiliation. In the process, they have also unearthed evidence from old cemeteries and prewar houses and the stories behind memorials erected for Holocaust victims. Drawing on the wealth of information these researchers have gathered, The Belarusian Shtetl creates compelling and richly textured portraits of the histories and everyday lives of each shtetl. Important for scholars and accessible to the public, these portraits set out to return the Jewish shtetls to their rightful places of prominence in the histories and legacies of Belarus"--